Differential Contributions of Prefrontal and Hippocampal Dopamine D1 and D2 Receptors in Human Cognitive Functions - Takahashi, Hidehiko; Kato, Motoichiro; Takano, Harumasa; Arakawa, Ryosuke; Okumura, Masaki; Otsuka, Tatsui; Kodaka, Fumitoshi; Hayashi, Mika; Okubo, Yoshiro; Ito, Hiroshi; Suhara, Tetsuya (The Journal of neuroscience, 2008)
Dopamine D1 receptors in the prefrontal cortex (PFC) are important for prefrontal functions, and it is suggested that stimulation of prefrontal D1 receptors induces an inverted U-shaped response, such that too little or too much D1 receptor stimulation impairs prefrontal functions. Less is known of the role of D2 receptors in cognition, but previous studies showed that D2 receptors in the hippocampus (HPC) might play some roles via HPC–PFC interactions. We measured both D1 and D2 receptors in PFC and HPC using positron emission tomography in healthy subjects, with the aim of elucidating how regional D1 and D2 receptors are differentially involved in frontal lobe functions and memory. We found an inverted U-shaped relation between prefrontal D1 receptor binding and Wisconsin Card Sorting Test performance. However, prefrontal D2 binding has no relation with any neuropsychological measures. Hippocampal D2 receptor binding showed positive linear correlations not only with memory function but also with frontal lobe functions, but hippocampal D1 receptor binding had no association with any memory and prefrontal functions. Hippocampal D2 receptors seem to contribute to local hippocampal functions (long-term memory) and to modulation of brain functions outside HPC (“frontal lobe functions”), which are mainly subserved by PFC, via the HPC–PFC pathway. Our findings suggest that orchestration of prefrontal D1 receptors and hippocampal D2 receptors might be necessary for human executive function including working memory.